Ethyl 3-(2-pyridyl)-2H-azirine-2-carboxylate : synthesis and reactivity with dienes - Alves, M. José (2005)
Ethyl 3-(2-pyridyl)-2H-azirine-2-carboxylate, the first example of an 3-heteroamatic-2H-azirine, was prepared and its reaction with conjugated 1,3-dienes, under mild conditions and in the absence of Lewis acid catalyst, produced cycloadducts in good yield and high stereoselectivity.